Efektivitas Penggunaan Metode Quantum Reading Terhadap Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Made Sri Astika Dewi; Ni Made Ignityas Prima Astuti; Nyoman Ayu Putri Lestari (STAHN Mpu Kuturan Singaraja, 2023)
This study aims to describe the effectiveness of using the Quantum Reading on the reading comprehension ability of sixth grade elementary school students. The results showed that the use of the Quantum Reading on students' reading comprehension skills was positive, students' reading comprehension skills using the Quantum Reading method showed better learning outcomes than before using the Quantum Reading. The results of inferential statistical analysis using the t test formula, it is known that thecalculated obtained is 7.3 with a frequency of dk = 26-1 = 25, at a significance level of 5% obtained ttable = 2.05. So, tcount > ttable or the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. This proves that the use of the Quantum Reading effective on the reading comprehension ability of Grade VI elementary school students